Asymptomatic shedding and subsequent transmission of genital herpes simplex virus. Issue 2 (April 1987) - Barton, S E; Davis, J M; Moss, V W; Tyms, A S; Munday, P E
Abstract : We report the transmission of genital herpes simplex virus (HSV) infection from an asymptomatic woman shedding virus from the cervix to two male sexual partners and further transmission from these two men while their infection was in the prodromal phase. The value of the restriction enzyme analysis of viral deoxyribonucleic acid (DNA) is presented. Guidelines regarding the management of patients who are found to be asymptomatic shedders of HSV are discussed.